Mild and severe diabetic ketoacidosis in children: a report of two cases - Vini Jamarin; Nanis Sacharina Marzuki (Paediatrica Indonesiana, 2022)
Diabetic ketoacidosis (DKA) is a severe complication of diabetes mellitus (DM) in children caused by insulin deficiency. This condition is often unidentified or diagnosed late, and treated with inadequate therapy. Diabetic ketoacidosis can lead to several complications, the most fatal being cerebral edema. We present two cases of DKA with different clinical presentation and severity. Early identification and proper management of DKA can help improve outcomes and avoid complications.